PROSPERITIES AND EFFECTS OF THE CRIME OF MONEY LAUNDERING - Dr. Dhafer A. Khashan (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Money laundering was a different crime than other crimes.The money laundering process needs special methods from modern and modern means, which uses advanced technologies by specialists and professionals in the field of technology and electronic sciences, in order to complete the merging process between criminal and non-criminal activities. Those means and methods create a set of criminal networks of an international character, which was characterized by coordination and organization at its highest levels, this was what we do not find in ordinary crimes, which was often characterized by individuality and simplicity of the means of implementation. Also, the crime of money laundering has negative effects on the global economy. Where its physical corner extends to more than one country.